Developing a Curriculum for Addressing the Opioid Crisis: A National Collaborative Process. (April 2022) - Kolomitro, Klodiana; Graves, Lisa; Kirby, Fran; Turnnidge, Jennifer; Hastings Truelove, Amber; Dalgarno, Nancy; van Wylick, Richard; Stockley, Denise; Mulder, Jeanne
BACKGROUND: The burgeoning use of opioids and the lack of attention to the safe prescribing, storage, and disposal of these drugs remains a societal concern. Education plays a critical role in providing a comprehensive response to this crisis by closing the training gaps and empowering the next generation of physicians with the knowledge, skills, and resources needed to diagnose, treat and manage pain and substance use. Curricular Development: The Association of Faculties of Medicine of Canada (AFMC) developed a competency-based, bilingual curriculum for undergraduate medical students to be implemented in all Canadian medical schools. The authors describe the principles and framework for developing a national curriculum. The curriculum design process was situated in the Knowledge to Action theoretical framework. Throughout the development of this curriculum, different stakeholder groups were engaged, and their needs and contexts were considered. CONCLUSION: The curriculum ensures that consistent information is taught across all medical schools to educate future physicians on pain management, opioid stewardship and substance use disorder.